2(1+2b)+6(b+5)=b-8+1+6b

Simple and best practice solution for 2(1+2b)+6(b+5)=b-8+1+6b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(1+2b)+6(b+5)=b-8+1+6b equation:



2(1+2b)+6(b+5)=b-8+1+6b
We move all terms to the left:
2(1+2b)+6(b+5)-(b-8+1+6b)=0
We add all the numbers together, and all the variables
2(2b+1)+6(b+5)-(7b-7)=0
We multiply parentheses
4b+6b-(7b-7)+2+30=0
We get rid of parentheses
4b+6b-7b+7+2+30=0
We add all the numbers together, and all the variables
3b+39=0
We move all terms containing b to the left, all other terms to the right
3b=-39
b=-39/3
b=-13

See similar equations:

| 14/7=k/8 | | 6u+4(u+8)=34 | | -6u+4(u+8)=33 | | 2(1+2b)+6(b+5=b-8+1+6b | | 3x+30=12x | | 1y-8y+56=2 | | 75+x/5=79 | | 2(6-7p)+2(p-7)=-38 | | 3s+9=1s-4 | | m÷5+6=9 | | 5(-x+5)-6(x-3)=-34 | | (24p-66)/3=3p+43 | | 9/11y=3/7 | | -20=x+16 | | 11/12=2/4h | | (1/3)(24p-66)=3p+43 | | x/2+x/5=2.1 | | |3x-21|=0 | | 1-8x=5(-x-5)+5 | | 24+6x=-6+6(x+6) | | -5(3x-17)=2(x-15)-55 | | 1x-13=7x-19 | | n3−5=12 | | -10-2y=30 | | 2n+20=5(6n+4) | | 18+4x=5(-x+2)-37 | | 2n+20=(6n+4) | | 4(c+6)-2c=-1 | | 6x+29=203 | | 4x+29=148 | | -21m+6=-3(7m-2) | | n÷9=13;n= |

Equations solver categories